2021
DOI: 10.3390/brainsci11010121
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Motor Cortex Plasticity by Repetitive Paired-Pulse TMS at Late I-Wave Intervals Is Influenced by Intracortical Excitability

Abstract: The late indirect (I)-waves recruited by transcranial magnetic stimulation (TMS) over primary motor cortex (M1) can be modulated using I-wave periodicity repetitive TMS (iTMS). The purpose of this study was to determine if the response to iTMS is influenced by different interstimulus intervals (ISIs) targeting late I-waves, and whether these responses were associated with individual variations in intracortical excitability. Seventeen young (27.2 ± 6.4 years, 12 females) healthy adults received iTMS at late I-w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
(69 reference statements)
3
22
0
Order By: Relevance
“…Second, this pattern of responsesimulatenuously suggesting that late I-waves were (MEPPA) and were not (MEPAP) responsive to iTMScan only be consistent with the more contemporary interpretation that different current directions recruit from different intracortical populations (for review, see; [54]). As previous work has shown that AP MEPs are potentiated by iTMS in isolation [44], our results therefore suggest that tDCSCB influenced (reduced) the neuroplastic response of intracortical circuits activated by AP stimulation. Despite this, given the delayed onset latency of MEPAP suggests that these responses primarily involved late I-waves (Table 3), it is unclear if tDCSCB is also able to infleunce the neuroplastic response of early I-waves recruited with AP stimulation.…”
Section: Cb Influence On Intracortical Excitabilitysupporting
confidence: 80%
See 4 more Smart Citations
“…Second, this pattern of responsesimulatenuously suggesting that late I-waves were (MEPPA) and were not (MEPAP) responsive to iTMScan only be consistent with the more contemporary interpretation that different current directions recruit from different intracortical populations (for review, see; [54]). As previous work has shown that AP MEPs are potentiated by iTMS in isolation [44], our results therefore suggest that tDCSCB influenced (reduced) the neuroplastic response of intracortical circuits activated by AP stimulation. Despite this, given the delayed onset latency of MEPAP suggests that these responses primarily involved late I-waves (Table 3), it is unclear if tDCSCB is also able to infleunce the neuroplastic response of early I-waves recruited with AP stimulation.…”
Section: Cb Influence On Intracortical Excitabilitysupporting
confidence: 80%
“…Previous work applying iTMS in isolation reported increased SICF post-intervention [21, 44]. Specifically, iTMS 1.5 has been demonstrated to potentiate SICF at ISIs of 1.5 ms and 4.5 ms [21], whereas iTMS 4.5 has been shown to potentiate SICF at ISIs of 4 - 5 ms [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations